Strengthening Legal Framework for Wildlife Poaching Prevention in Indonesia: Peningkatan Kerangka Hukum untuk Pencegahan Perburuan Liar Satwa Liar di Indonesia - Saxti, Muhammad Bima; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2025)
General Background: Indonesia possesses one of the world’s richest biodiversities but faces a severe decline in wildlife populations due to poaching and illegal trade. Specific Background: The escalation of poaching activities has disrupted ecosystems and reduced protected species, demanding effective legal protection. Knowledge Gap: Previous studies focused mainly on poaching causes and enforcement issues, yet few examined the comprehensive legal urgency from Indonesia’s positive law perspective. Aims: This study analyzes the urgency of legal protection against wildlife poaching based on Indonesian positive law. Results: The findings show that existing regulations such as Law No. 5/1990 and Government Regulation No. 7/1999 provide a clear foundation for protecting endangered species but require stronger enforcement, community involvement, and synchronization among institutions. Novelty: This research emphasizes the integrative role of legal instruments in ensuring wildlife sustainability through both in situ and ex situ conservation. Implications: Strengthened law enforcement and public awareness are vital to preserving biodiversity and maintaining ecological balance. Highlight: Emphasizes Indonesia’s legal framework for wildlife protection. Identifies enforcement and awareness gaps in anti-poaching efforts. Recommends integrative conservation through law and community roles. Keywords: Legal Protection, Wildlife, Poaching, Conservation Law, Indonesia